‘Suicide rates in Crete, Greece during the economic crisis: the effect of age, gender, unemployment and mental health service provision’ - Maria Basta; Alexandros Vgontzas; Anastasia Kastanaki; Manolis Michalodimitrakis; Katerina Kanaki; Katerina Koutra; Maria Anastasaki; Panagiotis Simos (BMC Psychiatry, 2018)
Abstract Background Recently, suicides in Greece have drawn national and international interest due to the current economic crisis. According to published reports, suicides in Greece have increased up to 40% and Crete has been highlighted as an area with the sharpest increase. Aim To investigate the suicide mortality rates in Crete between 1999 and 2013 and their association with the economic crisis. Methods Data on suicides were selected from the Department of Forensic Medicine files of the University of Crete. Results Our analysis showed that (1) Crete, has the highest suicide mortality rate in Greece, however no significant increase was observed between 1999 and 2013, (2) there were opposing trends between men and women, with women showing a decrease whereas men showed an increase in that period, (3) there was a significant increase of suicides in middle-aged men (40–64 yrs) and elderly, although the highest unemployment rates were observed in young men and women, and (4) finally, there was a regional shift of suicides with a significant decrease in Western Crete and a significant increase in Eastern Crete. Conclusions Although, Crete has the highest suicide mortality rates in Greece, we did not observe an overall increase during the last 15 years, including the period of economic crisis. Furthermore, there was an increase in middle-aged and elderly men, whereas young men and women showed oppositional trends during the years of austerity. This may be related to the culturally different expectations for the two genders, as well as that younger individuals may find refuge to either strong family ties or by immigrating abroad. Finally, the relative increase of suicides in Eastern Crete may be explained by factors, such as the lack of community mental health services in that area.